Body fat percentage, mid-upper arm circumference, and menstrual cycle in female students at X high school - Nuriannisa, Farah; Namira, Faradila Putri (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
Background: Irregular menstrual cycle in adolescent girls is an indicator of reproductive organ disorders. One of the risk factor for menstrual cycle disorders is nutritional status problem. Nutritional status can be measured using several anthropometric indicators such as body fat percentage and mid-upper arm circumference (MUAC).Objectives: This study aimed to analyze the correlation between body fat percentage and MUAC with the menstrual cycle in girls of X High School Sidoarjo.Methods: The type of this research was cross-sectional. The sample used 66 students with stratified random sampling technique. Body fat percentage was obtained by using the Mi Body Composition Scale 2, mid-upper arm circumference (MUAC) was measured by using midline, and the menstrual cycle was obtained by using a menstrual cycle questionnaire for the last 3 months. Data were analyzed with Rank Spearman test.Results: The results showed that average of body fat percentage was 26.8%, MUAC was 23.8 cm, and menstrual cycle was 35 days. Based on the test of the relationship between body fat percentage and the menstrual cycle, p-value 0.000 (r-value -0.875) were obtained, while MUAC and the menstrual cycle showed p-value 0.000 (r-value -0.916). The higher the body fat percentage, the shorter the menstrual cycle. The smaller the MUAC, the longer the menstrual cycle.Conclusions: There was a significant relationship between body fat percentage and MUAC with the menstrual cycle within girls in X High School Sidoarjo. Adolescent girls are expected to maintain normal nutritional status in order to maintain the regularity of their menstrual cycle, so as to minimize the risk of infertility in the future.